Pra-rancangan Pabrik Anilin dengan Proses Hidrogenasi Nitrobenzena Fase Uap Kapasitas 1.120 Ton/Tahun - Dita Shofia Khoirunissa’ (Fakultas Teknik, 2024)
Currently, the industrial sector plays a crucial role in boosting a country's economy, particularly within the manufacturing industry. One sector with significant potential to drive economic growth in Indonesia is aniline production. Aniline is an organic compound with the chemical formula C₆H₅NH₂. It is a colorless oily liquid with a distinctive odor, commonly used in pesticides, rubber, pharmaceuticals, and dyes. Up to now, Indonesia has been importing aniline from abroad, despite many domestic industries requiring it as a raw material. Therefore, this research discusses the design of an aniline plant with a capacity of 1,120 tons per year and an operational period of 330 days. The process stages include raw material preparation, aniline synthesis, and purification. The raw materials used are nitrobenzene and hydrogen, with annual quantities of 1,900.467 tons/years and 5,701.4020 tons/years, respectively. The process employed is vapor-phase hydrogenation with a yield of 99%. The proposed plant location is in Tanara District, Serang Regency, Banten.The planned business entity is a limited liability company (PT) with a total workforce of 202 employees. The feasibility of establishing the plant is based on an economic analysis that considers several financial parameters. According to the economic evaluation, the time required to recover the initial investment, or Pay-Out Time (POT), is 4.51 years; the Rate of Return on Investment (ROI) is 79.74%; and the Break-Even Point (BEP) is 53.04%. Keywords: Industrial, Aniline, Hydrogenation.
Reaploud Repository February_Hasyim
Keywords: Pabrik Anilin; Hidrogenasi Nitrobenzena; Fase Uap